Industrial Arts in the Junior High School Purposes, Objectives, Observable Behaviors. A Guide for Teachers of the Maryland Plan for Industrial Arts - Regimbal, Thomas; Maryland Univ., College Park. Dept. of Industrial Education ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1976)
This booklet is designed to aid teachers who are using the Maryland Plan, a program of industrial arts designed to be useful with junior high students who have diverse interests, capabilities, and aspirations. The main purpose of the guide is to aid in program development and specification of observable, measurable behaviors for accountable instruction. Contents include a definition of industrial arts, and discussion of goals and purposes, the program, objectives, student behavior, and measurable outcomes. The major portion of the guide consists of observable student behaviors for each of three units: The Anthropological Unit, The Group Project Approach, and Line Production Approach. Within each unit behaviors are listed under each of five sub-headings: Understanding the nature of industry and technology, self exploration, intellectual growth, skill development, and interpreting the changing nature of industry and technology. An appendix contains a Maryland Plan development model and lists resource materials and films on the Maryland Plan. (Author/HD)
Educational level discussed: Junior High Schools.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Behavioral Objectives; Curriculum Development; Industrial Arts; Junior High School Students; Junior High Schools; Resource Materials; State Programs; Student Behavior; Teaching Guides; Trade and Industrial Education; Maryland Plan; Guides, General